2012
DOI: 10.1590/s0100-879x2011007500160
|View full text |Cite
|
Sign up to set email alerts
|

MTP -493G/T gene polymorphism is associated with steatosis in hepatitis C-infected patients

Abstract: The reduction of hepatic microsomal transfer protein (MTP) activity results in fatty liver, worsening hepatic steatosis and fibrosis in chronic hepatitis C (CHC). The G allele of the MTP gene promoter, -493G/T, has been associated with lower transcriptional activity than the T allele. We investigated this association with metabolic and histological variables in patients with CHC. A total of 174 untreated patients with CHC were genotyped for MTP -493G/T by direct sequencing using PCR. All patients were negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…However, in a study with 174 Brazilian patients from the northeastern region, the G allele was more often present in patients infected with genotype 1 who had higher levels of fibrosis. Additionally, the GG and GT genotypes were considered independent protective factors against steatosis in patients with chronic hepatitis C and HCV genotype 1 and non-1 [32]. Finally, Saad et al [9] also studied this polymorphism, although not in relation to steatosis, and they reported an association between the GT and TT genotypes and severe fibrosis and cirrhosis ( P  = 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study with 174 Brazilian patients from the northeastern region, the G allele was more often present in patients infected with genotype 1 who had higher levels of fibrosis. Additionally, the GG and GT genotypes were considered independent protective factors against steatosis in patients with chronic hepatitis C and HCV genotype 1 and non-1 [32]. Finally, Saad et al [9] also studied this polymorphism, although not in relation to steatosis, and they reported an association between the GT and TT genotypes and severe fibrosis and cirrhosis ( P  = 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving women treated with a western type diet, higher fasting levels for plasma cholesterol (but not synthesis) and high-absorption status were demonstrated in TT homozygote women compared with G carriers (36). The presence of the G allele of MTTP -493G/T has an association with lower hepatic MTTP expression, which protects against steatosis in chronic hepatitis (37). Now, it is universally acknowledged that the MTTP -493G>T polymorphism is correlated with the risk of NAFLD.…”
Section: Microsomal Triglyceride Transfer Protein (Mttp)mentioning
confidence: 97%
“…We reviewed the titles and abstracts of all articles and excluded 20 articles; full-texts and data integrity were also reviewed, and 16 additional articles were excluded. Finally, 11 case-control studies that met all of the inclusion criteria were included in this meta-analysis (Namikawa et al, 2004;Petit et al, 2006;Gambino et al, 2007;Zampino et al, 2008;Mirandola et al, 2009;Carulli et al, 2009;Oliveira et al, 2010;Musso et al, 2007Musso et al, , 2010El-Koofy et al, 2011;Siqueira et al, 2012). Publication years ranged from 2004-2012.…”
Section: Baseline Characteristics Of Studies Includedmentioning
confidence: 99%
“…The MTP -493G>T polymorphism results from a G>T substitution in the intron region of NM_000253.2. Several previous studies have suggested that the MTP -493G>T polymorphism plays critical roles in the pathogenesis of NAFLD (Namikawa et al, 2004;Musso et al, 2007;Gambino et al, 2007;Zampino et al, 2008;Mirandola et al, 2009;Oliveira et al, 2010;Musso et al, 2010;El-Koofy et al, 2011;Siqueira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation